Storytelling with Music in Initial Teacher Education: A Comparative Study between Braga (Portugal) and Galicia (Spain) - Rocío Chao-Fernández; Sara Reis da Silva; Carol Gillanders (MDPI AG, 2023)
Although there is an indeterminacy in terminology, we can understand adding sounds and music to children's stories as the relationships created between verbal language (words), music language (sounds or silence), and body language (gestures and movements), that intertwine, strengthening the message intended to be communicated and allowing learning to be addressed in a holistic manner. This quantitative study, of a descriptive nature, aims to identify the previous experiences of student teachers in Galicia and the northern region of Portugal, related to putting sounds to children's stories and the training received in this field during their university studies. The data suggest that creative practices related to storytelling through music or adding sounds to children's stories and/or creating atmospheres in early childhood and primary education, despite providing great benefits, are neither as usual nor as enriching as would be expected, at least in the Spanish context. In relation to initial teacher education, the results are even less encouraging in both contexts, as the majority of students had received training in creating sound stories but stated that they were not satisfied with their experiences, as they did not believe they were trained or had acquired the necessary tools for the integration of this methodological strategy in the school classroom.